Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Handphone Oppo Pada Toko Mustika Rivel Maumere - Carlos Den Mage; Antonius Philipus Kurniawan; Yosef Tonce (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aims to: (1) find out the picture of Purchase Decisions, Product Quality and Price; (2) analyze the influence of Product Quality and Price on Purchase Decisions both partially and simultaneously. The population in this study is Oppo mobile phone consumers who are domiciled in the Sikka Regency area. Because the population is not limited, 100 people were sampled. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is carried out through the F test and the t test. The results of the descriptive analysis show that the Purchase Decision variable is in the criteria is quite good, the Product Quality variable is in the good criteria, then the Price variable is in the good criteria. The statistical results of the t-test show that partially the Product Quality variable has a positive and significant effect on Purchase Decisions. The results of the determination analysis showed that the two independent variables in this study were able to explain the variation of the up and down of Purchase Decisions at the Mustika Rivel Maumere Store by 54.9% while 45.1% was influenced by other factors outside the research variables.